Systematic Literature Reviews: Why I Rejected Your Review - Crawford, Joseph (Journal of University Teaching and Learning Practice, 2025)
Systematic literature reviews (SLRs) have become an increasingly common methodological approach in higher education research, particularly within the Journal of University Teaching and Learning Practice (JUTLP). However, despite their popularity, a significant proportion of submitted SLR manuscripts are desk-rejected prior to peer review. This Commentary critically examines recurring methodological shortcomings that often undermine the credibility and rigour of these submissions. Drawing on best practices in evidence synthesis, the paper highlights five core areas where authors frequently fall short: (1) the formulation of research questions that are appropriately scoped, answerable, and aligned with review goals; (2) the development of transparent, valid, and replicable search strategies using Boolean logic, truncation, and multiple databases; (3) the implementation of systematic screening and selection processes, including use of PRISMA flow diagrams and clear inclusion/exclusion criteria; (4) the use of trustworthy and replicable methods of data extraction and synthesis, including quality appraisal of included studies; and (5) the articulation of meaningful implications that extend beyond descriptive summaries to offer theoretical, empirical, and practical contributions. Through these insights, the Commentary seeks to provide constructive guidance for researchers and reviewers, with the aim of enhancing methodological integrity and increasing the acceptance rate of SLR submissions to JUTLP and similar journals. By strengthening methodological transparency, reliability, and relevance, Systematic reviews can serve as powerful tools to synthesise evidence, guide pedagogical innovation, and inform higher education policy.